2014
DOI: 10.1002/pssb.201451168
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electrical and mechanical properties of nanographite electrodes for supercapacitors by addition of nanofibrillated cellulose

Abstract: Graphene and porous carbon materials are widely used as electrodes in supercapacitors. In order to form mechanically stable electrodes, binders can be added to the conducting electrode material. However, most binders degrade the electrical performance of the electrodes. Here we show that by using nanofibrillated cellulose (NFC) as a binder the electrical properties, such as capacitance, were enhanced. The highest capacitance was measured at an NFC content of approximately 10 % in ratio to the total amount of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 19 publications
1
37
0
Order By: Relevance
“…Graphene has been recognised as a promising material that will revolutionise science and engineering. Nanographite (NG), in contrast, is a heterogeneous carbon material comprising a mixture of graphene, a few multi-layer graphene flakes, and graphite (Blomquist et al 2016;Andres et al 2014). It can be recognised as a highly functional conductive carbon nanoparticles that can be tailored for specific applications such as batteries, supercapacitors, graphite-based composites, printed electronics, sensors, energy applications, and life-science applications (Blomquist et al 2016).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Graphene has been recognised as a promising material that will revolutionise science and engineering. Nanographite (NG), in contrast, is a heterogeneous carbon material comprising a mixture of graphene, a few multi-layer graphene flakes, and graphite (Blomquist et al 2016;Andres et al 2014). It can be recognised as a highly functional conductive carbon nanoparticles that can be tailored for specific applications such as batteries, supercapacitors, graphite-based composites, printed electronics, sensors, energy applications, and life-science applications (Blomquist et al 2016).…”
Section: Introductionmentioning
confidence: 98%
“…Andres et al (2014) showed that a 10 % addition of nanofibrillated cellulose (NFC) to the NG improved both wet and dry strength while maintaining the capacitance. Malho et al (2012) reported that NFC could be used in aerogels, composites, and other hybrid materials; they used NFC together with multi-layer graphene (1.25 wt%) to improve the mechanical properties of the nanocomposite, with the resulting material having a Young's modulus 16.9 GPa, ultimate strength of 351 MPa, and work of fracture of 22.3 MJm -3 .…”
Section: Introductionmentioning
confidence: 98%
“…Andres et al demonstrated how the introduction of NFC in graphite-based supercapacitors not only enhanced the capacitance of the devices but also improved their lifetime by acting as a mechanically supporting matrix which prevented cracking of the graphite during cycling measurements. [72] There are also many reports of paper-based batteries which have the same advantages as supercapacitors. [82][83] The flexibility of such paper devices has resulted in a completely new battery device concept: origami batteries.…”
Section: Paper Electronicsmentioning
confidence: 99%
“…Nanofibrillated cellulose (NFC) water suspensions have been shown to have excellent colloidal stabilizing properties for both graphite particles and CNT, making it possible to produce high quality conductive papers. [71][72] Conductive polymers can be composited with paper either by adding it in the form of a liquid suspension or by direct polymerization onto the cellulose fibers in solution or on paper. [73][74][75][76] It has been demonstrated that the type of cellulose and the surface charge of the fibers have a strong influence on the quality of the polymer coating on paper and hence the conductivity.…”
Section: Paper Electronicsmentioning
confidence: 99%
See 1 more Smart Citation